Childhood obesity leads to adult type 2 diabetes and coronary artery diseases: A 2-sample mendelian randomization study. Issue 32 (August 2019) - Fang, Xuqian; Zuo, Junli; Zhou, Jingqi; Cai, Jialin; Chen, Changqiang; Xiang, Enfei; Li, Haibo; Cheng, Xiaoyan; Chen, Peizhan
Abstract : Abstract: Observational studies have reported that childhood obesity is positively associated with risks of type 2 diabetes (T2D) and coronary artery disease (CAD) in adults; however, whether this association is causal is still unclear. In the present study, we conducted the 2-sample Mendelian randomization (MR) studies to investigate whether childhood obesity is causally associated with T2D and CAD in adults. Seven single-nucleotide polymorphisms (SNPs) that significantly associated with childhood obesity were used as instrumental variables. The 2-sample MR analyses were performed with the summary-level data of large-sample genome-wide association studies to evaluate the causal effects of childhood obesity on adult T2D and CAD and the levels of cardiometabolic traits. The 2-sample MR analyses suggested that each 1-unit increase in the log-odds of having childhood obesity was causally associated with an increased risk of adult T2D (odds ratio [OR] = 1.16, 95% confidential interval [CI] = 1.06–1.28; P = 1.0 × 10 –3 ) and CAD (OR = 1.07, 95% CI = 1.02–1.12; P = 4.0 × 10 –3 ) based on the inverse-variance weighted method. The MR analyses also suggested that childhood obesity was positively associated with the levels of adult body mass index, waist circumference, hip circumference, waist and hip ratio, log-transformed fasting glucose, log-transformed homeostatic model assessment (HOMA) of insulin resistance (%), and triglycerides. The childhood obesity was negatively associated with the adult high-density lipoprotein cholesterol level; however, there was no evidence of a causal association between childhood obesity and the levels of fasting glucose, 2-hour glucose, HbA1c (%), log-transformed HOMA of ß-cell function (%), low-density lipoprotein cholesterol, or total cholesterol in adults. In conclusion, a genetic predisposition to childhood obesity was associated with an increased risk of adult T2D and CAD, providing causal relations between childhood obesity and the risks of T2D and CAD in adults; however, the results need to be validated with larger-scale intervention studies. Abstract : Supplemental Digital Content is available in the text